The Role of the Merit System in Improving the Professionalism of ASN - Astrid Indah Maretha Dewi; Lalu Tirangga Aji Wangsanegara (Civic Governance and Public Administration, 2025)
This study discusses the application of the merit system in an effort to improve the professionalism of the State Civil Apparatus (ASN) in Mataram City. The merit system is an important instrument in realizing a bureaucracy that is professional, accountable, and free from non-professional intervention. This study found that the implementation of the merit system in Mataram City has encouraged the improvement of the quality of civil servants through a more objective and performance-based process of recruitment, promotion, and career development. However, there are still a number of challenges, such as the limitations of independent assessment centers, the lack of optimal digitization of SIMPEG, and organizational culture that does not fully support meritocracy. For this reason, there needs to be policy support and comprehensive system improvement so that the implementation of the merit system can run more effectively and sustainably, so as to be able to strengthen the performance of civil servants and the quality of public services.